Thermal Adaptation A Theoretical and Empirical Synthesis - Piyaphongkul, Dr. Jiranan (Journal of Food Health and Bioenvironmental Science, 2018)
There are thousands of books written about biology, ecology, molecular biology, etc., but few have been written by thermal biologists. This book, written by Michael J. Angilletta Jr., is an ambitious and successful attempt to integrate the various subjects of biology, ecology, physiology, and behavior into a clear understanding of the fundamental concepts; it is remarkably free of error of confusion. This book has 289 pages of text that are divided among its nine chapters. As its title implies, the book illustrates principles of thermal biology with broad scopes such as an overview of evolutionary thermal biology, key terms and definition, concepts, and implementation of thermal biology research related to climate change issues. The most important question for readers is “Who would benefit from reading this book?” This book contains many excellent examples, case studies, and photos that help illustrate the points and help readers understand what thermal biology is all about and also provide excellent ideas for scientists who are planning and engaging in research. As such, this book is probably a worthwhile purchase for graduate students, academics and researchers. I hope you will enjoy reading this book and find it useful.